Dehairing of Patagonian cashmere-bearing goat fleeces: yields and quality characteristics of textile products and by-products - Sacchero, Diego Mariano (2025)
Dehairing is the mechanical separation of coarse fibers, considered contaminants, from fine fibers of high textile value. This process is crucial in the transformation of double-coated animal fibers such as cashmere. This study evaluated the performance of different fleece types (cashmere and cashgora) from Creole Neuquina goats during the dehairing stage. Yields, diameters, and the proportion of coarse and fine fiber fractions, as well as fiber lengths before and after dehairing, were compared. The dehairing yield of cashmere was 8.9%, while that of cashgora reached 15.0%. Although the process reduced the coarse fiber content, a considerable proportion remained in the final product (3.8% and 6.6% for cashmere and cashgora, respectively). Expressed as hauteur, the reduction in the initial staple length was 46% in cashmere and 42% in cashgora, resulting in mean values of 26.8 and 27.6 mm.